Methodology implemented for the 3d-seismic modelling using gocad and norsar 3d software applied to complex areas in the llanos foothills (2007)
A methodology has been applied in order to use seismic modeling and generate synthetic data which are compared with results from field data. This methodology has been applied to the Sirirí area andsubsequently it has been extended to other geographic areas. To fully develop this methodology, the GOCAD and 3D NORSAR software packages were used to build respectively the geological and 3D seismic models. This methodology involves making structural modeling by edition of the different objects (horizons and faults) in the structural module of GOCAD, with the help of available seismic and well data, in order to be consistent with reality. From this result a valid seismic model is imported to NORSAR 3D for making the seismic modeling, using ray tracing to get synthetic data. Finally, this information is compared with field data that has been processed.